What factors hamper innovation amongst SMEs in Kenya? - Abbey, E.; Adu-Danso, E. (Taylor & Francis Group, 2022)
While much of the evidence about innovation amongst SMEs in many developing countries have sought to examine the factors that enhance the propensity of a firm to innovate, far less effort has gone into assessing the factors that hamper it. This paper follows the latter literature to provide an explanation of firm innovation failure amongst SMEs in Kenya by focusing exclusively on external obstacles. By relying on the World Bank Enterprise Surveys and defining innovation as involving product and process innovation, we showed that factors such as political instability and infrastructure, measured as access to electricity, can be critical to firm innovation. We also found that the effects could be context-specific, as the results differ based on various firm characteristics, including firm type, sector, age and size. Our findings provide important policy implications about firm innovation in Kenya as well as the understanding that providing a more conducive business environment is not only critical to enhancing various firm activities but also enhancing innovation performance.
Research Article
Keywords: Kenya; firm innovation; obstacles